Arbuscular Mycorrhiza Augments Arsenic Tolerance in Wheat (Triticum aestivum L.) by Strengthening Antioxidant Defense System and Thiol Metabolism - Sharma, Surbhi; Anand, Garima; Singh, Neeraja; Kapoor, Rupam (Frontiers in Plant Science, 2017)
Arbuscular mycorrhiza (AM) can help plants to tolerate arsenic (As) toxicity. However, plant responses are found to vary with the host plant and the AM fungal species. The present study compares the efficacy of two AM fungi Rhizoglomus intraradices (M1) and Glomus etunicatum (M2) in amelioration of As stress in wheat (Triticum aestivum L. var. HD-2967). Mycorrhizal (M) and non-mycorrhizal (NM) wheat plants were subjected to four levels of As (0, 25, 50, and 100 mg As kg-1 soil). Although As additions had variable effects on the percentage of root colonized by the two fungal inoculants, each mycobiont conferred benefits  to the host plant. Mycorrhizal plants continued to display better growth than NM plants. Formation of AM helped the host plant to overcome As-induced P deficiency and maintained favorable P:As ratio. Inoculation of AMF had variable effects on the distribution of As in plant tissues. While As translocation factor (TF) decreased in low As (25 mg kg-1 soil), it increased under high As (50 and 100 mg As kg-1 soil). Further As translocation to grain was reduced (As grain:shoot ratio) in M plants compared with NM plants. Arsenic-induced oxidative stress (generation of H2O2 and lipid peroxidation) in plants reduced significantly by AMF inoculation. The alleviation potential of AM was more evident with increase in severity of As stress. Colonization of AMF resulted in higher activities of the antioxidant enzymes (superoxide dismutase, catalase and guaiacol peroxidase). It increased the concentrations of the antioxidant molecules (carotenoids, proline, and α-tocopherol) than their NM counterparts at high As addition level. Comparatively higher activities of enzymes of glutathione-ascorbate cycle in M plants led to higher ascorbate:dehydroascorbate (AsA:DHA) and glutathione: glutathione disulphide (GSH:GSSG) ratios. Inoculation by AMF also augmented the glyoxalase system by increasing the activities of both glyoxalase-I and glyoxalase-II enzymes. Mycorrhizal colonization increased concentrations of cysteine, glutathione, non-protein thiols, and activity of glutathione-S-transferase that facilitated sequestration of As into non-toxic complexes. The study reveals multifarious role of AMF in alleviation of As toxicity.